Region-specific variation and determinants of caesarean delivery among ever-married women in Bangladesh - Gobinda Karmakar; Md. Tariqujjaman; Aklima Alam; Md Ahshanul Haque; Nurun Nahar Naila; Tahmeed Ahmed (PLoS ONE, 2025)
Background The extensive use of caesarean delivery has adverse consequences for both maternal and neonatal health. This study aims is to investigate regional variation and identify region-specific determinants of caesarean deliveries among ever-married women in Bangladesh. Methods A total of 17,704 women aged 15–49 who had given birth to children within three years preceding each of the surveys were included in this study, based on the last four consecutive nationally representative surveys between 2011 and 2022. Various demographics and socio-economic variables were considered as exposure variables. Bivariate and multiple mixed-effects logistic regression models were used to draw inferences from the data. Results In Bangladesh, between 2011 and 2022, the percentage of caesarean deliveries increased threefold (15% to 46%). Additionally, more than half of the children born in Dhaka and Khulna were via caesarean deliveries. After adjusting for relevant covariates in each of the region-specific models, women with highly educated husbands had significantly higher odds of undergoing a caesarean delivery compared to those with less educated husbands in Barisal (OR: 4.48), Chattogram (OR: 2.69), and Rangpur (OR: 2.46) divisions. The likelihood of caesarean delivery was considerably higher among overweight or obese women in Dhaka and Sylhet (OR: 2.33 and 2.50), as well as among women living in households with higher wealth status than their counterparts in Sylhet and Khulna (OR: 2.95 and 2.22), respectively. Conclusion Policymakers can address the high rate of caesarean deliveries by targeting several key factors at various geographic levels. Raising family awareness about the benefits of normal delivery can encourage expectant parents to make informed choices. They should also ensure the quality of care provided in hospitals, ensuring that medical professionals follow evidence-based guidelines for childbirth. Furthermore, implementing a centralized or local pregnancy registration system may enhance the monitoring and access to maternal health services.